Answer: I got this answer wrong but I go two right look at the step by step explanation
Hopefully that helped a little
Step-by-step explanation:
The expression (x + 5) is a factor of given function f(x) So the remainder of the function will be zero.
Remainder theorem:
The given function,
[tex]f(x) = x^3+3x^2-25x-75[/tex]
Equate (x + 5) is equal to 0.
x + 5 = 0
x = -5
Substitute x = -5 in given equation.
[tex]f(x) = x^3+3x^2-25x-75\\\\f(-5) = -5^3+3(-5)^2-25(-5)-75\\\\f(-5) = 0[/tex]
Since f(-5) = 0. thus, (x + 5) is a factor of given function f(x).
Learn more about the remainder theorem here:
https://brainly.com/question/1550437
#SPJ2